The increasing longevity gap by lifetime earnings and its distributional implications - Daniel Kemptner; Peter Haan; Holger Lüthen (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We use social security records to document heterogeneity in life expectancy by lifetime earnings and we analyze how this longevity gap has evolved over cohorts. We provide evidence that the earnings-related longevity gap is increasing over cohorts in West Germany. Further, we propose a decomposition to disentangle the role of increasing earnings inequality over cohorts and the effect of changes in the earnings gradient. Finally, we study the distributional implications for the pension system.
Keywords: H55; I14; J11; 330